Comparison Analysis of Customer Experience in Robo-advisor Vs. Human Trader in Making Finacial Decision in the Trading Using Customer Journey Mapping Method - Noviani, Stefani Dwi; Windasari, Nila Armelia (Journal of Business and Management, 2020)
Abstract. Robo-advisor is a kind of financial technology established since 2008. In this research, the Robo-advisor used for playing trading forex. Generally, users who do not know about forex trading will use Robo-advisor as their financial decision-maker, it is possible that users as human-trader can play this forex trading manually. Therefore, the purpose of this study is to determine the comparison of financial risks, captured emotions, and the final decision of Robo-Advisor users and human-traders based on experience with the customer journey mapping method in playing forex trading. The researcher used eleven respondents for this study, consisting of eleven Robo-advisor respondents and four human-trader respondents, which then conducted online questionnaires and semi-structured interviews to obtain data used to start making touchpoints  as a basis for mapping customer journeys. The results obtained indicate that Robo-advisor's financial risk can no longer be changed because it is based on a predetermined algorithmic system, and the users' average emotions are happy and will continue to use Robo-advisor as a financial decision-maker. While human traders can adjust their choices as they do personal analysis and show that they prefer to manually play forex trading compared to Robo-Advisor. Therefore users of Robo-Advisor will continue to use Robo-advisor and human-traders will continue to manually play forex trading.Keywords: Artifical Intelligence, Customer Experience, Customer Journey Mapping, Finansial Decision Making, Robo-Advisor